Pelatihan Public Speaking sebagai Upaya Peningkatan Kepercayaan Diri Siswa di SMPN 15 Banjarmasin - Tri Reski Muchtar; Anisa Fitria; Abdul Hadi Hardian; Alfina Ramadhanti; Daut Yahya; Sudirwo Sudirwo; Anna Nur Faidah (Jurnal Pengabdian Masyarakat Waradin, 2026)
Public speaking skills are an essential competency that plays an important role in students’ personal development. However, many junior high school students still experience challenges such as low self-confidence when speaking in public. This community service activity aims to improve students’ self-confidence and verbal communication skills through structured public speaking training at SMPN 15 Banjarmasin. The method applied was Participatory Action Research (PAR) with a quantitative approach involving 27 students as participants. The training program included interactive material on the fundamentals of public speaking, anxiety management techniques, non-verbal communication, and hands-on practice sessions. Evaluation was conducted using pre-test and post-test instruments to measure improvement in students’ knowledge and skills. The results showed a significant increase in the students’ average scores, from 85.37 before the training to 95.15 after the training. These findings indicate that the public speaking training program effectively builds self-confidence and enhances students’ communication skills during adolescence.